Effect of Menopause on Lipid Profile and Apolipoproteins - R.K. Swapnali; Ravikiran Kisan; D.S. Jayaprakash Murthy (Al Ameen Medical College, 2011)
Menopause is an estrogen deficient state. Natural menopause confers a threefold increase in Coronary Artery Disease (CAD) risk. This study was conducted to assess the effect of menopause on serum lipid profile and apolipoproteins. About 123 healthy subjects were studied (62 premenopausal and 61 postmenopausal women). Total Cholesterol (TC), Triglycerides (TG) and High Density Lipoprotein (HDL) were estimated by enzymatic method and Apo A-I and Apo B were estimated by immunoturbidimetric method by semi-autoanalyzer. TC, TG, Very Low Density Lipoprotein (VLDL), Low Density Lipoprotein (LDL), Apo B, TC/HDL and Apo B/Apo A-I were increased, whereas HDL and Apo A-I were decreased in postmenopausal women when compared to premenopausal women and were statistically significant (p < 0.001). Apo A-I and HDL cholesterol are antiatherogenic whereas Apo B and LDL cholesterol are atherogenic. The cholesterol content of HDL and LDL as an indicator for risk of CAD may be misleading because the cholesterol content varies with a variety of physiological and pathological conditions but not their protein content. Hence estimation of Apo A-I and Apo B, the protein part of HDL and LDL respectively serves as a more reliable tool in predicting the risk of CAD in postmenopausal women.